New arsenate minerals from the Arsenatnaya fumarole, Tolbachik volcano, Kamchatka, Russia. VIII. Arsenowagnerite, Mg2(AsO4)F. (28th August 2018) - Pekov, Igor V.; Zubkova, Natalia V.; Agakhanov, Atali A.; Yapaskurt, Vasiliy O.; Chukanov, Nikita V.; Belakovskiy, Dmitry I.; Sidorov, Evgeny G.; Pushcharovsky, Dmitry Yu.
ABSTRACT: A new mineral arsenowagnerite, Mg2 (AsO4 )F, the arsenate analogue of wagnerite, was found in sublimates of the Arsenatnaya fumarole at the Second scoria cone of the Northern Breakthrough of the Great Tolbachik Fissure Eruption, Tolbachik volcano, Kamchatka, Russia. It is associated closely with johillerite, tilasite, anhydrite, hematite, fluorophlogopite, cassiterite, calciojohillerite, aphthitalite and fluoborite. Arsenowagnerite occurs as equant to tabular crystals up to 1 mm across combined in interrupted crusts up to 0.1 cm × 1.5 cm × 3 cm. The mineral is transparent, light yellow, lemon-yellow, greenish-yellow or colourless and has a vitreous lustre. Arsenowagnerite is brittle, with Mohs hardness of 5. Cleavage is distinct, the fracture is uneven. D calc = 3.70 g cm –3 . Arsenowagnerite is optically biaxial (+), α = 1.614(2), β = 1.615(2), γ = 1.640(2) and 2Vmeas = 25(5)°. Wavenumbers of the strongest absorption bands in the IR spectrum (cm –1 ) are: 874, 861, 507, 491 and 470. The chemical composition (average of six electron-microprobe analyses, wt.%) is: MgO 38.72, CaO 0.23, MnO 0.32, CuO 0.60, ZnO 0.05, Fe2 O3 0.11, TiO2 0.03, SiO2 0.08, P2 O5 0.18, V2 O5 0.03, As2 O5 54.96, SO3 0.10, F 8.91 and –O=F –3.75, total 100.57. The empirical formula calculated on the basis of 5 (O + F) apfu is: (Mg1.98 Cu0.02 Mn0.01 Ca0.01 )Σ2.02 (As0.99 P0.01 )Σ1.00 O4.03 F0.97 . Arsenowagnerite is monoclinic, P 21 / c, a = 9.8638(3), b = 12.9830(3), c = 12.3284(3) Å, β = 109.291(3)°, V = 1490.15(7) Å 3 and Z = 16. The strongest reflections of the powder X-ray diffraction pattern [ d, Å( I )( hkl )] are: 5.80(41)(002), 5.31(35)(120), 3.916(37)( 2 21), 3.339(98)(221, 023), 3.155(65)(202), 3.043(100)( 1 41), 2.940(72)( 2 04), 2.879(34)( 3 22) and 2.787(51)(320, 1 24). The crystal structure was solved from single-crystal X-ray diffraction data, R = 0.0485. Arsenowagnerite is isostructural to wagnerite- Ma 2 bc . The crystal structure is built by almost regular AsO4 tetrahedra, distorted MgO4 F2 octahedra and distorted MgO4 F trigonal bipyramids.